Compassionate citizenship through storytelling – an analysis of stereotypical views among ladies’ residence students in Huis ten Bosch on Stellenbosch Campus - Turner, Chantel Julia (Stellenbosch : Stellenbosch University, 2017)
Thesis MA(VA)--Stellenbosch University, 2017.